Analisis Evaluasi Sumatif dalam Pembelajaran Tematik Siswa Kelas VI SDN Batujaya di Era Pandemi Covid-19 - Magdalena, Ina; Oktavia, Dela; Nurjamilah, Putri (ARZUSIN, 2021)
This study aims to analyze the summative evaluation of 6th grade thematic learners in the Covid-19 Pandemic Era. Regarding thematic learning which contains the learning process, learning assessment and learning evaluation must be based on student needs. The Summative Evaluation was carried out at the end of the semester, at SD Batujaya. This Summative Evaluation was carried out using a test technique. The technical test used is the details of the questions in the form of multiple choice and descriptions. The method used in this study is a qualitative method which tends to use analysis in the form of interviews, documentation and observations. In this online learning, the role of parents is very important in the teaching and learning process to replace a teacher in guiding student learning. The results of the study using summative evaluation in thematic learning in 6th grade elementary school are quite effective.